Spatial inequality and its relationship with local food environments: The case of Barcelona. (February 2020) - Garcia, Xavier; Garcia-Sierra, Marta; Domene, Elena
Abstract: Unhealthy dietary habits are affecting negatively the health status of citizens throughout the world. Reversing unequal local food environments, in terms of physical accessibility to food stores with healthy items, can be an effective way to mitigate the poor eating habits of the population and contribute to the sustainability of agri-food systems. The main objective of this study is to explore the characteristics of local food environments in the city of Barcelona (Catalonia, Spain), and to analyse the existence of sociodemographic inequalities in the access to food stores with or without supply of organic products. Based on an official database of commercial premises and on additional information, 7983 food stores have been identified and classified, 471 (5.9%) of which supply organic food. Spearman's Rho correlation and Local Indicator of Spatial Association (LISA) analyses are applied to investigate the global and local relationships between food access and two sociodemographic variables, namely Household Income Index and percentage of non-Spanish inhabitants. Results demonstrate that, even though total food access and organic food access are positively influenced by the socioeconomic level of the neighbourhoods, this is not the case in some areas of the city, where other factors might be more influential. Our findings emphasise the importance of local food environments in shaping health, and the need to promote its equality across different socioeconomically segregated areas to counterbalance negative effects on the health of vulnerable populations. Highlights: A total of 7.983 food stores in Barcelona are classified in 11 categories. The 5.9% are stores with organic food available. Neighbourhoods with a larger proportion of non-natives have better food access. Access to organic food is driven by socioeconomic status of neighbourhoods. Bivariate LISA shows that there are areas of the city where this is not applicable.